The Vote of the Big Man in Papua's Noken System: Indigenous Justice and Human Dignity - Nabila, Balgis; Luluardi, Yunas Derta (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The Noken system in Papua has generated significant debate regarding the balance between electoral democratic principles and Indigenous political traditions. Within this system, the Big Man holds a central position as the decision-maker for collective votes through structured community deliberation. Although frequently viewed as conflicting with the principle of “one person, one vote,” this practice represents an Indigenous conception of justice based on communal consensus and respect for leaders with strong moral legitimacy. This study aims to examine the role of the Big Man in the Noken system, its contribution to the protection of human dignity, and its relevance within Indonesia’s legal and democratic framework. Using a qualitative approach supported by literature review and analysis of Constitutional Court decisions, the research identifies that the legitimacy of the Big Man rests on a consistent record of service, the capacity to maintain social harmony, and customary authority recognized by the community. Findings indicate that the Noken system functions as a valid expression of cultural democracy when implemented in a participatory, transparent manner and when it accommodates individuals who choose to vote independently. This research offers a unique contribution by demonstrating the compatibility of Indigenous political mechanisms with human rights principles and by providing insights for strengthening electoral governance in Indigenous regions.